HUBUNGAN KOMPETENSI, BEBAN KERJA, DAN LOYALITAS KARYAWAN - Natalia Ika Eristaria; Joko Irawan; Nur Wening (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This study aims to analyze the correlation between competence, workload and employee loyalty. The analysis technique used in this study is product moment correlation method with questionnaire research instrument. The result of this study were obtained that competence has a significant relationship with employee loyalty, workload has a significant relationship with employee loyalty. Both competency and workload together have a significant influence on employee of 64,8%.